Propofol Promotes Blood-Brain Barrier Breakdown and Heat Shock Protein (HSP 72 kd) Activation in the Developing Mouse Brain - S. Sharma, Hari; Pontén, Emma; Gordh, Torsten; Eriksson, Per; Fredriksson, Anders; Sharma, Aruna (CNS & Neurological Disorders - Drug Targets, 2014)
Anesthetic agents induce cellular stress that may affect blood-brain barrier (BBB) permeability permeability in the developing brain causing brain dysfunction. In this investigation, effects of Propofol on cellualr stress using inducible heat shock protein (HSP72) and BBB breakdown employing albumin immunoreactivity in the mouse brain were examined. Propofol was administered to in mice on the postnatal day 10 once (10 mg/kg or 60 mg/kg subcutaneously). On the 75th day, HSP72 and albumin immunostaining were examined on 3-µm thick paraffin sections in the midbrain areas using standard protocol. Saline-treated and age-matched mice served as controls. Propofol dose-dependently produced a significant increase in the number of HSP72 and albumin-positive cells in cortex, hippocampus, thalamus and hypothalamus, a feature not seen in the saline-treated group. HSP72 and albumin activity in the propofol-treated group was largely confined to neurons and often localized to their cell cytoplasm and/or nucleus. HSP72 and albumin expression was the most prominent in cerebral cortex and in hippocampus, followed by hypothalamus and thalamus. These novel observations suggest that anesthetic agents, by inducing cellular stress in the developing brain may disrupt the BBB permeability that may have long lasting effects on adult brain function.
Keywords: developing brain